The NOISE CON 87 - Archives of Acoustics, Editorial Board (Archives of Acoustics, 1987)
"High Technology for Noise Control" was the theme of NOISE-CON 87, the 1987 National Conference on Noise Control Engineering. One hundred and twenty-five papers on technical topics on noise control engineering were presented at the three-day meeting which was held on the campus of The Pennsylvania State University in State College, Pennsylvania on 1987 June 8-10. Professor Jiri TICHY, Head of the Graduate Program in Acoustics at Penn State, was the General Chairman for the conference.